Luminescent guest encapsulated metal-organic framework composites for photonic sensing technology - Zhang, Y (2022)
Luminescent metal-organic frameworks (LMOFs) are promising hybrid materials and are considered ideal for fabricating sensors and optoelectronics. A unique direction of LMOFs research is to harness MOFs as ‘hosts’ to encapsulate various luminescent ‘guest’ (LG) molecules for producing LG@MOF systems. However, feasible design ideas and in-depth mechanism analyses are scarce, compromising their practical engineering potential. This section, combined with the structure, synthesis, types, and applications of LG@MOF systems, is described in detail in Chapter 1 and 2.